Light Transport: Anisotropic Light Transport in White Beetle Scales (Advanced Optical Materials 10/2015). Issue 10 (20th October 2015) - Cortese, Lorenzo; Pattelli, Lorenzo; Utel, Francesco; Vignolini, Silvia; Burresi, Matteo; Wiersma, Diederik S.
<x xml:space="preserve">Abstract</x> The nanostructured complex chitin network inside Cyphochilus white beetle scales is responsible for their exceptional bright whiteness. On page 1337, L. Cortese, D. S. Wiersma, and co‐workers show how, despite their low refractive index and extremely low thickness (around 7 micrometers), the scales reflect diffusively more than 70% of incident light. Such high reflectance is obtained by taking advantage of the optimized structural anisotropy of the chitin network. In this image a particular of the interior of two dissected scales is shown.